(3eONd GdYedjGJs - (3WGgQ eMSf(B, (3efUhQs; (3fYeI YHGS GdNaGLj(B, s ((3YeGf(B:s (3OGQ GdjGRhQj(B,s, 2010)
(3GdJMOjGJ GdJj JhGLg GdefXeGJ aj GdbQf GdMGOj h GdYTQjf , GdbjGOI h Jahb GdefXeGJ ` GdJZjjQ GdJfWjej , GdJWhjQ GdJfXjej , GdGHOGY h GdJYde GdJfXjej , eY hLhO CSFdIYGeI , CSFdI acQjI h CSFdI NjGQGJ eJYOOI(B.s
(3eQGLY U(B.225s
Keywords: (3EOGQI GdCYeGds; (3GdEOGQIs; (3GdbjGOIs; (3GdefXeGJs